Aksesibilitas Transportasi Dan Infrastruktur Bagi Penyandang Disabilitas - Amelia Rahmadhania Aman; Linatus Sururoh; Maharani Ariya; Muhammad Ananda Pratama; Siti Hamidah (Universitas Katolik Widya Karya Malang, 2023)
The reason of this research is the concern of persons with disabilities who demand their rights to be able to carry out their daily activities comfortably and easily accessible. Therefore, this article aims to help people with disabilities to get their rights with in-depth research on how good and equitable infrastructure is for people, especially people with disabilities. The data source for this research is the conclusion of several articles and journals that contain Accessibility and Infrastructure for Persons with Disabilities. The results are in the form of a discussion of the infrastructure itself and how good facilities are for persons with disabilities. The suggestions and recommendations that we can provide are optimizing, maximizing, maintaining, and repairing existing infrastructure in the environment and making it comfortable for persons with disabilities.